Sacred and transcendental organization development: Bricoluer of strategic suggestions for knowledge-based consultants. - Ahmad, Che Mahzan (INSI Publications, 2011)
In the 21st century, Organization Development (OD) is expected to awaken and grow the minds, hearts and spirits of managers and their organizations. We suggest sacred and transcendental approach for the above matter, in particular taking the wisdom of Sufism. OD then is being seen as a sacred sophialogical engagement with hikma as its base of action. Hikma is about putting/placing rightly thing at the right place in order for justices to prevail. It is also about taking actions of opposing stupidity and emotional disorders. Gulen noted that hikma begins with reflections, curiosity, understanding and zeal to study and search, and continues with obedience and worship, ending in spiritual pleasures and eternal happiness (saadah). A sophialogical engagement in the context OD is to bring practical wisdom (phronesis) as a moral goodness that connects knowledge and action. In enabling phronesis to be present, we suggest novelistic sacred inquiry is an instrument of practice. Meanwhile ta’wil is being proposed as the method of knowing/understanding data. Ta’wil is best described as a kind of Islamic hermeneutics. In ta’wil, spiritual and worldly experiences are utilized, and both exoteric and esoteric are considered. The basic aim of ta’wil is to cross the line of literal/exoteric meaning for a greater understanding/knowing beyond the sensual perceptions. We theorized two main axioms of ta’wil, namely active imagination and contemplation. Contextually, in this type of consultancy, consultants need to venture into nafsiology as part of their historicality of understanding. Nafsiology basically is a study that concerns with internal aspects of man. In this work we are emphasizing on nafs, qalb and ruh. In relation to the three compounds, being ghaflah (forgetfulness/heedlessness/neglectfulness) is considered as functional illness that needs to be rectified, and we recommend tazkiya as hikma of normality under the rubric of sacred learning action. As tazkiya is a work of an adult knower, we theorized three grammars of organizing, namely imagin.i.zation about the dynamics of order/disorder of the three compounds, reading and contemplating ayah (verbal and non-verbal signs) and eschatology as paradigm of living-life. Consultants in this regard must understand that the whole gamut mentioned above so far is to bring the desired future state of organizational well-being, saadah, within the reach of the acquired second. We present Gulenian dialogical Sufism as referential case study in the contemporary tradition.